The effectiveness of the Fetakgomo Thusong Service Centre in providing government services to the community of Fetakgomo - Nethathe, Azwinndini Yvonne Joy (My University, 2015)
Although South Africa’s economy is the largest and most developed in Africa, South Africans still face a challenge of access to government information and services. This is so as most people still reside in areas that are remote and predominately rural. The government introduced the Thusong Service Centre (TSC) programme, also known as one stop Centre’s in communities with the aim to improve the quality of people’s lives by bringing services closer to the people. The study seeks to explore the potential of Thusong Service Centre’s as an initiative of integrated service delivery. It looks at the effectiveness of the Fetakgomo Thusong Service Centre in providing adequate government services to the community of Fetakgomo. Furthermore, the study develops an understanding of Thusong Service Centre’s through an investigation of factors that can contribute towards a successful centre. One of the main findings of the research was that even though the Fetakgomo Thusong Service Centre is a good initiative it is still faced with operational challenges such as lack of institutional arrangement for departments rendering services at the centre.
Thesis (M.M. (Public and Development Management))--University of the Witwatersrand, Faculty of Commerce, Law and Management, Graduate School of Public and Development Management, 2015.